PROBLEMATIKA DAN MOTIVASI MENIKAHI WANITA MANAPOUSE DEMI KEUTUHAN RUMAH TANGGA MENURUT PERSEPSI MASYARAKAT KABUPATEN MUARA JAMBI - Siti Marlina; A. A. Miftah; Rahmi Hidayati; Dian Mustika (Indonesian Association of Islamic Family Law Lecturers, 2019)
Marriage is anyone's right as long as the marriage is in accordance with the Shari'a, women who are no longer menstruating are called menopause and in this phase women experience various changes, with this change the groom is expected to understand the problematics of marrying menopause women for the sake of continuing family integrity, to give an idea to a bride, especially a man who wants to marry a menopausal woman (who is no longer reproducible), this study aims to find out the problems and motivations of marrying a menopausal woman (not to be reproduced) and to know the review of Law No. 1 of 1974 and Islamic Law concerning marrying women manouse, this research is a qualitative research with an empirical normative sociological approach by using the interview method, with the technical writer asking the spouse directly as a respondent and from the results of the interview the writer is the data. The results of this study can be concluded First Problematics marrying menopausal women are: not getting offspring, changes in intimate partner relationships. and social impact in the community Second Motivation to marry menopausal women as follows: because they really want to get married, earn a living, undergo worship, have friends in old age and friends.